Far field superlensing inside biological media through a nanorod lens using spatiotemporal information - Mohamad J. Hajiahmadi (Nature Portfolio, 2021)
Abstract Far field superlensing of light has generated great attention in optical focusing and imaging applications. The capability of metamaterials to convert evanescent waves to propagative waves has led to numerous proposals in this regard. The common drawback of these approaches is their poor performance inside strongly scattering media like biological samples. Here, we use a metamaterial structure made out of aluminum nanorods in conjunction with time-reversal technique to exploit all temporal and spatial degrees of freedom for superlensing. Using broadband optics, we numerically show that this structure can perform focusing inside biological tissues with a resolution of λ/10. Moreover, for the imaging scheme we propose the entropy criterion for the image reconstruction step to reduce the number of required optical transducers. We propose an imaging scenario to reconstruct the spreading pattern of a diffusive material inside a tissue. In this way super-resolution images are obtained.